Internet of Things (IoT) Cybersecurity Challenges and Mitigation Mechanisms - Joshua Ebere Chukwuere (Khazanah Sosial, 2022)
This study deployed desktop research methodology in seeking to understand the cybersecurity challenges confronting Internet of Things (IoT) and the mitigation mechanisms. Objects are no longer independent from each other; rather, connectivity through the power of the internet has connected them. IoT is no longer a new invention or innovation in the technology industry and human lives. The concept is widely used in different industries such as healthcare, food, finance, manufacturing, government, insurance, oil and gas, transportation, postal services, defence, and many more. These industries are using the ability of IoT to function optimally in facilitating different activities. Users of technology devices use IoT devices in homes, offices, and other places to increase productivity and efficiency daily. This article analyses the cybersecurity challenges of IoT and its mitigation mechanisms. The findings identified different cybersecurity challenges confronting IoT and the ways to mitigate them.